Multiple Intelligences in Communication Classroom - Javed, Samra; Khan, Fouzia Naeem (JISR management and social sciences & economics, 2010)
The theory of multiple intelligences was put forward by Dr. Howard Gardner, who is a professor of education at Harvard, in 1983. The theory shifts our attention from the stereotyped conception of intelligence, based on I.Q. testing, to nine different intelligences so as to explain a diverse range of human potential. This paper will identify the type of intelligence each of the target group (students of Communication) has, identify the teaching methods used to teach the target group and find out whether the teaching methods cater to the type of intelligence the target group has. This study shows that target group is diverse in terms of multiple intelligences but the ranking of target group intelligence does not correlate with that of class activities used to teach these students. The linguistic intelligence, predominantly catered to in the class activities, was not the dominant intelligence in this group and the dominant intelligence.